Zika virus infection of Hofbauer cells. (14th December 2016) - Simoni, Michael K.; Jurado, Kellie Ann; Abrahams, Vikki M.; Fikrig, Erol; Guller, Seth
Abstract : Recent studies have linked antenatal infection with Zika virus (ZIKV) with major adverse fetal and neonatal outcomes, including microcephaly. There is a growing consensus for the existence of a congenital Zika syndrome (CZS). Previous studies have indicated that non‐placental macrophages play a key role in the replication of dengue virus (DENV), a closely related flavivirus. As the placenta provides the conduit for vertical transmission of certain viruses, and placental Hofbauer cells (HBCs) are fetal—placental macrophages located adjacent to fetal capillaries, it is not surprising that several recent studies have examined infection of HBCs by ZIKV. In this review, we describe congenital abnormalities associated with ZIKV infection, the role of HBCs in the placental response to infection, and evidence for the susceptibility of HBCs to ZIKV infection. We conclude that HBCs may contribute to the spread of ZIKV in placenta and promote vertical transmission of ZIKV, ultimately compromising fetal and neonatal development and function. Current evidence strongly suggests that further studies are warranted to dissect the specific molecular mechanism through which ZIKV infects HBCs and its potential impact on the development of CZS.